2001
DOI: 10.1111/j.1572-0241.2001.04684.x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal permeability is increased in a proportion of spouses of patients with Crohn's disease

Abstract: Small intestinal permeability is increased in a proportion of healthy spouses of patients with Crohn's disease. The presence of abnormal permeability studies in patients with Crohn's disease and a proportion of their healthy close contacts suggests that this phenomenon is caused by environmental factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 40 publications
2
23
0
1
Order By: Relevance
“…This idea is certainly consistent with the recent observations by Swidsinski and colleagues (29). Alternatively, alterations in barrier function (30,31) or intrinsic innate immune responses (32,33) may enhance the likelihood of the response to these flagellin molecules in patients prone to develop IBD.…”
Section: Discussionsupporting
confidence: 79%
“…This idea is certainly consistent with the recent observations by Swidsinski and colleagues (29). Alternatively, alterations in barrier function (30,31) or intrinsic innate immune responses (32,33) may enhance the likelihood of the response to these flagellin molecules in patients prone to develop IBD.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, the epithelium must form a selectively permeable barrier that allows absorption of nutrients, electrolytes, and water while preventing passage of noxious luminal contents. This barrier is disrupted in many diseases, including inflammatory bowel disease, graft versus host disease, and infectious enterocolitis (1)(2)(3)(4)(5)(6). While some have suggested that this barrier dysfunction is a central component of disease pathogenesis (7)(8)(9), other work suggests that barrier dysfunction may be a secondary event that does not contribute to disease progression (10).…”
Section: Introductionmentioning
confidence: 99%
“…The maintenance of the mucosal barrier integrity is believed to be fundamental in preventing the induction of dysregulated immunity induced by microbes and other luminal components. The importance of the mucosal barrier in the pathogenesis of IBD is supported by the findings that intestinal permeability is altered in some first-degree relatives with Crohn's disease and that intestinal permeability precedes a flare of IBD (9,17,51). We have previously shown that trefoil factor (TFF) peptides contribute to mucosal barrier function by protecting the gastrointestinal mucosa from injury and promoting repair after an injury has occurred (2,13,14,23,35).…”
mentioning
confidence: 75%